Effects of an integrated safety system for swivel seat arrangements in frontal crash - Li, Zhao; Gao, Ruth; McCoy, Robert; Hu, Hongyu; He, Lei; Gao, Zhenhai (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Autonomous vehicle (AV) open a way to the arrangement of swivel seat in a vehicle, which could pose a challenge to traditional safety systems. The integration of Automated emergency braking (AEB) and pre-pretension (PPT) seatbelt is to improve occupant protection. The objective of this study is to explore the integrated safety system control strategies for swiveled seating orientations. Methods: Occupant restraints were examined in various seating configurations using a single seat model with a seat mounted seatbelt. A seat orientation was set from -45° to 45° with 15° increment. A pretension was used on shoulder belt to represent an active belt force cooperated with AEB. A generic full frontal vehicle pulse of 20mph was applied to the sled. The occupant’s kinematics response under various integrated safety system control strategies were analyzed by extracting a head pre-crash kinematics envelope. The injury values were calculated for various seating directions with or without an integrated safety system at the collision speed of 20mph. Results: In a lateral movement, the excursions of dummy head were 100 mm and 70 mm in the global coordinate system for negative and positive seat orientations. In axial movement, the head travelled 150mm and 180 mm in the global coordinate system for positive and negative seating directions. The 3-point seatbelt did not restrain the occupant symmetrically. The occupant experienced greater y-axis excursion and smaller x-axis excursion in negative seat position. Various integrated safety system control strategies leaded in significant difference in head movement in y direction. The integrated safety system reduced the potential injury risks of an occupant in different seating positions. When the AEB and PPT were activated, the absolute HIC15, BrIC, Nij and the chest deflection were reduced in most seating directions. However, the pre-crash increased the injury risks at some seating positons. Conclusions: The pre-pretension seatbelt could reduce the occupant’s forward movement in the rotating seat positions in a pre-crash period. The occupant’s pre-crash motion envelope was generated, which could be beneficial to future restraint system and vehicle interior design. The integrated safety system could reduce injuries in different seating orientations.